LIGHT-TAILED DISTRIBUTIONS ESTIMATION IN AUTO-ACCIDENT CLAIMS - SIEGERS YOBELIANO (NIM: 10113099), GERRY
Talking about insurance company, claim is the main problem which has to be calculated carefully. Claim is the amount of money the policy holder asked based on the terms of the insurance policy and under certain condition. Furthermore, we have to know what kind of distribution the claim amount like in order to understand the characteristics of the claim. In this study, we will compare the claim amount’s data using the light – tail distribution. The data was obtained from certain insurance company about auto-accident claim amount. There are two candidate light-tail distributions such as gamma and Weibull which used fitting the data. Each distribution will be applied using data with outlier. Each data distribution will be tested using manual procedures and some statistics programs. The goal of this study is to make understanding between light – tail distribution and claim amount in certain insurance company.